Maqashid Sharias Study on the Practice of Selling Gold that Has Not Been Paid off in Conditions of Urgent Need - Sy, Miftahul Zikri; Iska, Syukri (Denisya Smart Consulting, 2025)
This study aims to analyze the practice of buying and selling gold on credit from a sharia perspective, focusing on the principles of justice, transparency, and avoidance of elements of usury, gharar, and fraud. This phenomenon is becoming increasingly relevant as the public